Le Théâtre de la mort de Tadeusz Kantor : un « gué secret » entre les vivants et les morts - Virginie Lachaise (Conserveries Mémorielles)
It would be tempting to place the whole Tadeusz Kantor’s theater under the sign of the revenance and haunting, so everything is back : the characters, situations, objects, spaces, words and sounds, almost all returning the autobiographical sphere and the religious history and mythology of Poland, homeland of the artist. In the confined space of its Chamber of memory and imagination, the scene, the artist made a machine to view the past spring to the rhythm of ”heartbeat memory“ Children in tatters, the spectra of the family who do not allow themselves to forget, the scraps of old battles Cricot 2. They are ”snapshots“ ”fingerprints“ that overlap each other in the mode of repetition and variation and draw an anamorphic and fleeting reality, the image of the mental space of the author. Because for this eternal recurrence occurs, it is necessary that the body wants. On the set of threshold, Kantor book that fascinated her scopic drive and plunged fantastically ”the other side“ of the illusion, in the past, which he alone is real.But death has no other means to show that borrowing the life ways, this artistic conviction, a belief in Kantor literally borrowed from the Yiddish culture, leads to a conception of the condition of the unprecedented player. Inhabited by the dead, it is required to act as a puppet of flesh, like a ghost, haunted by the wandering soul of a dybbuk.